Tumekung Dan Healing Touch Terhadap Tingkat Kecemasan Ibu Hamil Primigravida Trimester III - Risyanti, Berty; Novianti, Silvi Teni; Indriati, Maya; Hartiningsih, Siti Sugih (Madu : Jurnal Kesehatan, 2024)
One frequent mental condition that many pregnant women experience is anxiety. Anxiety is a natural response to perceived danger, but it may progress to a major mental health issue if it becomes chronic and gets in the way of everyday functioning. As a consequence of their concerns about giving birth and their ability to care for their newborns afterwards, seven out of ten primigravida pregnant women surveyed in a pilot study during annual prenatal exams reported experiencing anxiety. Tumekung and healing touch are two non-pharmacological approaches to anxiety treatment. The purpose of this research was to find out how tumekung and healing touch affected the anxiety levels of first-time mothers in their third trimester of pregnancy. Two research groups, one for experiments and one for controls, make up this study's quasi-experimental design. Using the Paired T test and the Independent T-Test, we may analyse both univariate and bivariate data. With a p-value of 0.00 <0.05, which is less than the degree of error, the analytical test rejects H0 and accepts H1. In conclusion, pregnant women at the Padasuka Health Centre in Bandung City's Cibenying Kidul District reported significantly lower anxiety levels after receiving tumekung and healing touch